1998
DOI: 10.1590/s0103-90161998000300020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do método de triagem para análise de milho contaminado com aflatoxinas pela fluorescência amarelo-esverdeada brilhante (BGYF- Bright Greenish Yellow Fluorescence)

Abstract: A técnica da fluorescência amarelo-esverdeada brilhante (BGYF) como método de triagem na avaliação de milho eventualmente contaminado com aflatoxina, utilizada por uma indústria alimentícia do Estado de São Paulo em 61 amostras de milho, foi comparada com a técnica BGYF padronizada, aplicada em laboratório antes e após trituração dos grãos e, também, com a técnica da cromatografia em camada delgada (CCD). Os resultados da indústria geraram menor número de resultados falso-positivos do que a técnica BGYF padron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Comparisons were carried out with ELISA and TLC methods for AFB 1 in samples of corn, feed and peanut (106) and for AFs, OTA and ZEA in corn and corn meal (63); two TLC methods for OTA in green coffee (66); and TLC and HPLC methods for AFM 1 in milk (116) and for FB S in corn (80). Screening methods for AFs in corn and peanut were also evaluated (44,83,119). A sampling scheme was proposed for AF analysis in grains (29) and anomalous recoveries of AF from peanut and Brazil nuts measured by ELISA was reported (26).…”
Section: Analytical and Mycological Methodsmentioning
confidence: 99%
“…Comparisons were carried out with ELISA and TLC methods for AFB 1 in samples of corn, feed and peanut (106) and for AFs, OTA and ZEA in corn and corn meal (63); two TLC methods for OTA in green coffee (66); and TLC and HPLC methods for AFM 1 in milk (116) and for FB S in corn (80). Screening methods for AFs in corn and peanut were also evaluated (44,83,119). A sampling scheme was proposed for AF analysis in grains (29) and anomalous recoveries of AF from peanut and Brazil nuts measured by ELISA was reported (26).…”
Section: Analytical and Mycological Methodsmentioning
confidence: 99%
“…The bright greenish yellow fluorescence (BGYF) was related as an efficient method for grain and nuts decontamination (Shotwell at al., 1975;Pearson et al, 2001), and it has been used by industries for sorting contaminated grains (Palomino et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified defects in nuts and grains by measuring their color alteration, some caused by fungi . Apart from color, another way of sorting deterioration in nuts (pistachio, peanuts, cashew nuts, almonds, and macadamia) and grains (corn, soybean, and wheat) is by detecting toxin fluorescence and also by detecting the bright greenish yellow fluorescence, a fluorescence produced by kojic acid from fungi in the kernel ,, . However, the latest and very promising method for inner nut and grain deterioration detection is by near infrared (NIR) spectrophotometry ,,, .…”
Section: Introductionmentioning
confidence: 99%